ANALISIS PENDAPATAN USAHA IKAN MAS SISTEM KERAMBA JARING APUNG DAN PEMASARANNYA DI KABUPATEN SIMALUNGUN - Sumantri, Bambang; Sriyoto, .; Maria, Sumantri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2005)
This research was aimed at estimating the level of earnings and efficiency obtained by farmer of goldfish with floating net cage system and to investigating the form of marketing channel from floating net cage system from Kelurahan Haranggaol to consumer in Kabanjahe Kabupaten Karo. This research executed in Kelurahan Haranggaol, Kecamatan Haranggaol Horisan, Kabupaten Simalungun, North Sumatera. Fourty samples of goldfish farmer with floating net cage system were slected using simple random sampling method. R/C ratio marjin marketing analysis were used to answer the research purposes. Research resulted farmer carred Rp 107.461.246,06 per season or with R/C ratio of 1,83. The marketing channel from Kelurahan Haranggaol to consumer in Kabanjahe is identified one channel pattern, that is, compiler merchant to dealers on Kabanjahe and than to Consumer in Kabanjahe. The marjin of marketing is equal to Rp 900 at merchant of compiler and Rp 1.850 at dealer.Total of marketing marjin is equal to Rp 2.750.